Prosperous Justice Party (PKS) Image Management In The 2019 Election - Fahmi Azhari Siregar; Gun Gun Heryanto; Munadhil Abdul Muqsith; Refly Setiawan (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
Abstract:Prosperous Justice Party (PKS) is one of the largest Islamic-based parties in Indonesia. Ahead of the 2019 general election, PKS received an internal solidity endurance test and externally as the government's opposition. PKS requires communicative performance to improve its image in the 2019 election. Departing from these problems, researchers are interested in knowing how the PKS communicative performance in the 2019 legislative elections and the PKS Political Public Relations Approach in the 2019 elections. This research uses the main theories of communicative performance, which Michael Pacanowsky and Nick O'Donnell-Trujillo and the concept of Public Relations Politics to explain the management of the PKS image in the 2019 legislative elections. This study uses qualitative research methods, with library studies, documentation, and interviews. Besides, this research also uses the Norman Fairclough critical paradigm approach. The object of this research study is the board of the Central Prosperous Justice Party (DPP PKS) Board of Representatives and PKS Legislative Members in the Indonesian House of Representatives (DPR). The findings of this research indicate, Communicative Performance of PKS in the 2019 Election in Ritual Performance, each party's decision making is collective. Political Public Relations Approach is not maximized in a political marketing approach, and it needs its management to improve the image of PKS. The results of this study indicate that PKS is weak in issue management, and PKS Communicative Performance in the 2019 elections is quite good even though the performance of persuasion is less effective. Also, the Persuasive Political approach is less effective for PKS.Keywords: Image Management, Prosperous Justice Party (PKS), 2019 Elections Abstrak:Partai Keadilan Sejahtera (PKS) adalah salah satu partai berbasis Islam terbesar di Indonesia. Menjelang Pemilu 2019, PKS mendapatkan uji ketahanan internal soliditas dan secara eksternal sebagai oposisi pemerintah. PKS menuntut kinerja komunikatif untuk meningkatkan citranya di Pemilu 2019. Berangkat dari permasalahan tersebut, peneliti tertarik untuk mengetahui bagaimana kinerja komunikatif PKS pada Pemilu Legislatif 2019 dan Pendekatan Humas Politik PKS pada Pemilu 2019. Penelitian ini menggunakan teori utama kinerja komunikatif yaitu Michael Pacanowsky dan Nick O'Donnell-Trujillo serta konsep Public Relations Politics untuk menjelaskan pengelolaan citra PKS pada Pemilu Legislatif 2019. Penelitian ini menggunakan metode penelitian kualitatif, dengan studi pustaka, dokumentasi, dan wawancara. Selain itu, penelitian ini juga menggunakan pendekatan paradigma kritis Norman Fairclough. Objek penelitian ini adalah pengurus Dewan Perwakilan Rakyat Partai Keadilan Sejahtera Pusat (DPP PKS) dan Anggota Legislatif PKS di Dewan Perwakilan Rakyat Indonesia (DPR). Temuan penelitian ini menunjukkan, Kinerja Komunikatif PKS pada Pemilu 2019 dalam Pelaksanaan Ritual, pengambilan keputusan masing-masing pihak bersifat kolektif. Pendekatan Political Public Relations belum dimaksimalkan dalam pendekatan pemasaran politik, dan perlu pengelolaannya untuk meningkatkan citra PKS. Hasil penelitian ini menunjukkan bahwa PKS lemah dalam pengelolaan isu, dan Kinerja Komunikatif PKS pada Pemilu 2019 cukup baik meskipun kinerja persuasi kurang efektif. Selain itu, pendekatan Politik Persuasif kurang efektif untuk PKS.Kata Kunci: Pengelolaan Citra, Partai Keadilan Sejahtera (PKS), Pemilu 2019